AHP 10: Story: A Stolen Journey - Blo bzang tshe, ring (Asian Highlands Perspectives, 2018)
BIo bzang tshe ring (b 1984) is from A mgon Village, A mchog Town, Bsang chu County, Kan Iho Tibetan Autonomous Prefecture, Kan su'u Province. He says, "I wrote this story based on what I was told by the three men who brought the main character of the story to Zi ling City in their car."